2002
DOI: 10.1074/jbc.m109946200
|View full text |Cite
|
Sign up to set email alerts
|

TGTCACA Motif Is a Novel cis-Regulatory Enhancer Element Involved in Fruit-specific Expression of the cucumisin Gene

Abstract: Cucumisin, a subtilisin-like serine protease, is expressed at high levels in the fruit of melon (Cucumis melo L.) and accumulates in the juice. We investigated roles of the promoter regions and DNA-protein interactions in fruit-specific expression of the cucumisin gene. In transient expression analysis, a chimeric gene construct containing a 1.2-kb cucumisin promoter fused to a ␤-glucuronidase (GUS) reporter gene was expressed in fruit tissues at high levels, but the promoter activities in leaves and stems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…It comprises more than 10% of the total juice protein and is synthesized in the central parts of the fruits (3). Cucumisin is synthesized and accumulated only in melon fruits, and a cis-regulatory enhancer element in the cucumisin promoter regulates fruit-specific expression of the cucumisin gene (4). We have determined the complete nucleotide sequence of a cucumisin cDNA, the first sequenced plant serine protease, and found that cucumisin is a member of the subtilisin (EC 3.4.21.62) superfamily characterized by a catalytic triad of three amino acids: Asp, His, and Ser (5).…”
mentioning
confidence: 99%
“…It comprises more than 10% of the total juice protein and is synthesized in the central parts of the fruits (3). Cucumisin is synthesized and accumulated only in melon fruits, and a cis-regulatory enhancer element in the cucumisin promoter regulates fruit-specific expression of the cucumisin gene (4). We have determined the complete nucleotide sequence of a cucumisin cDNA, the first sequenced plant serine protease, and found that cucumisin is a member of the subtilisin (EC 3.4.21.62) superfamily characterized by a catalytic triad of three amino acids: Asp, His, and Ser (5).…”
mentioning
confidence: 99%
“…In the cases of E254367 (flower-and fruit-specific) and E541096 (flower specific) promoters, there were several flower-and pollen-related regulatory elements (VOZATVPP, Mitsuda et al, 2004;POLLEN1LELAT52, Bate and Twell, 1998;AGAMOUSATCONSENSUS, Shiraishi et al, 1993). In particular, we found that E254367 contains fruitspecific cis-elements (TGTCACACUCUMSIN, Yamagata et al, 2002;Fig. 3A).…”
Section: Isolation Of the Regulatory Regions Of Five Tissue-specific mentioning
confidence: 92%
“…Various lengths of soybean CHR promoter, Arabidopsis CHS promoter, and tomato CAB7 promoter (Bowler et al 1994a) were amplified by PCR using two primers containing XbaI and BamHI sites at their upstream-and downstream-ends, respectively, and introduced into XbaIBamHI sites of pSKGUS3C (Yamagata et al 2002). Two synthesized oligonucleotides for both strands of CaMV 35S minimal promoter (-46 to ?8), 35S(-46) ?…”
Section: Particle Bombardmentmentioning
confidence: 99%
“…For the gain-of-function analysis, the upstream region of the CHR promoter between nucleotides -600 to -186 relative to the transcription start site was amplified by PCR using the primers, GmchrproA-Fw1; 5 0 -GGGGTCTAGATA CCATATTTGGATTTG-3 0 and GmchrproA-Rv4; 5 0 -GGGGTCTAGAACAAATGTTTTCAACATT-3 0 with pGmCHRproA as a template, and the product was subcloned into the XbaI site of p35S (-46) GUS3C, after which the direction of the promoter was verified by sequencing. pBIXFF (Yamagata et al 2002) harboring the firefly luciferase (LUC) reporter gene under the control of the CaMV 35S promoter was used as an internal control. Gold particles (1.0 lm in diameter) were coated with 2.5 lg of pBIXFF and an equimolar amount of each promoter-GUS construct by ethanol precipitation according to the manufacturer's protocol (Bio-Rad Laboratories Inc., Hercules, CA, USA).…”
Section: Particle Bombardmentmentioning
confidence: 99%
See 1 more Smart Citation